A Mechanically Reinforced Super Bone Glue Makes a Leap in Hard Tissue Strong Adhesion and Augmented Bone Regeneration (Adv. Sci. 11/2023). Issue 11 (14th April 2023) - Hu, Shanshan; Wang, Shan; He, Qingqing; Li, Dize; Xin, Liangjing; Xu, Chuanhang; Zhu, Xingyu; Mei, Li; Cannon, Richard D.; Ji, Ping; Tang, Han; Chen, Tao
Abstract : Mechanically Reinforced Super Bone Glue "Nvwa Patches up the sky" is one of the ancient myths of China. According to legend, in ancient times, the sky and the earth collapsed. The goddess "Nvwa" smelted five‐color stone to patch up the sky, flattened the flood, killed the beast, and last rescued all people. In article number 2206450, Ping Ji, Han Tang, Tao Chen, and co‐workers construct a mussel inspired super bone glue (L‐DPZ2), like five‐color stone in the hands of "Nvwa", which can repair the humans' hard tissue and promote the bone healing. This super bone glue is like "Nvwa's" mercy, which can benefit a large number of clinical patients.